Trends in Vietnam's pork supply and structural features of its pig sector - Tisdell, C.A. (Bentham Science Publishers Ltd., 2009)
Pork is the single most important source of animal protein in Vietnam and its availability has a substantial impact on the well-being of the Vietnamese. Since 1996, the local supply and per capita availability of pork in Vietnam have increased substantially. The trends in and sources of this growth in supply are identified by analysing official statistics. Differences in regional supply of pork are also identified, as well as regional variations in pork yields. Vietnam`s pork industry relies on many small-scale household producers for the bulk of its pork supply. The structure of the sector is investigated and found to be altering slowly – a slight increase in scale of production units has been occurring. The rate of growth in Vietnam`s supply of pork has slowed and production could decline despite the large increases in productivity in this sector since the mid-1990s. The industry is still not internationally competitive. Hence, imports of pork from Canada and the USA occurred in the last few years, and these may increase after 2012 when Vietnam should become World Trade Organization (WTO)-compliant. This concerns the Government of Vietnam because it could threaten the economic sustainability of its pig industry. The Government believes that by adopting policies to increase the scale of production of individual pig-producing units, this will shore up the competitive position of its pig sector. This policy is discussed.